2010
DOI: 10.1038/modpathol.2010.107
|View full text |Cite
|
Sign up to set email alerts
|

Clinical setting and extent of premortem evaluation do not predict autopsy discrepancy rates

Abstract: Autopsy rates have been affected by a number of factors, including technological advances and clinician beliefs of the diminished value of the autopsy. Such factors have resulted in a cultural shift in medicine away from the autopsy. Despite this shift, a number of studies have shown significant differences between antemortem clinical diagnoses and postmortem findings. Surveys of clinician beliefs about the autopsy have pointed toward antemortem diagnostic advancements as an important factor in declining rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 11 publications
(6 reference statements)
1
25
0
2
Order By: Relevance
“…More than a powerful tool for quality improvement in patient care, the autopsy generates accurate vital statistics, provides a better understanding of diseases, and drives progress in medicine . The procedure, which has changed little since the 19th century, consists of macroscopic observation, such as evisceration and measurement of the major organs, followed by histological analysis . Many physicians worldwide are concerned about decreased autopsy rates, which are assumed to be at least partially caused by clinical disinterest.…”
mentioning
confidence: 99%
“…More than a powerful tool for quality improvement in patient care, the autopsy generates accurate vital statistics, provides a better understanding of diseases, and drives progress in medicine . The procedure, which has changed little since the 19th century, consists of macroscopic observation, such as evisceration and measurement of the major organs, followed by histological analysis . Many physicians worldwide are concerned about decreased autopsy rates, which are assumed to be at least partially caused by clinical disinterest.…”
mentioning
confidence: 99%
“…at the time of their last hospital admission, there were 3 patients in terminal stage and 1 in premortem 17 found similar rates of clinical-pathological discrepancy in three clinical settings that differed in the amount of antemortem diagnostic workup, thus refuting the hypothesis that the availability of diagnostic procedures decreases the frequency of discrepancies in the diagnosis. a systematic review by Shojania et al 2 concluded that the capacity of the autopsy to identify diagnoses unsuspected before death is high enough as to reinforce the recommendation of performing autopsies.…”
Section: Respiratory Findings At Autopsymentioning
confidence: 88%
“…With the superabundance of sophisticated and high-technology diagnostic testing available, it is widely assumed that autopsy rarely reveals any important undetected conditions, but the hypothesis that only the lack of testing leaves important conditions undiagnosed was recently tested by a study comparing the rate of finding major undiagnosed conditions at autopsy in patients who died in intensive care units, inpatient surgical units, and nursing homes [7]. The rate of finding major undiagnosed conditions was 27.8% for the medical intensive care unit patients, 32.7% for the surgery service patients, and 31.3% for the nursing home patients ( P = .84).…”
Section: Discussionmentioning
confidence: 99%